Intracellular Replication Inhibitory Effects of Tea Tree Oil on Vesicular Stomatitis Virus and Anti-inflammatory Activities in Vero Cells - Shao, Qi; Huang, Junjie; Li, Jingui (Frontiers in Veterinary Science, 2021)
Viral disease management has proven difficult and there are no broadly licensed vaccines or therapeutics. Vesicular stomatitis virus (VSV) is an active pathogen of wild ungulates and livestock, its infection frequently caused irreversible vesicles on the tongue or other positions, then leading to enormous economic loss. Tea tree oil (TTO) has been shown a popular remedy for many skin diseases owing to its antibacterial, antipruritic and anti-inflammatory effects. However, the potential effect of TTO on VSV proliferation and the corresponding inflammatory response in cells remains unclear. In this study, MTT assay was used to evaluate the cytotoxicity of TTO, and Reed Muench method was applied to obtain the Tissue culture infective dose 50 (TCID50) of VSV in Vero cells. Then fluorescence observation, RT-qPCR, Western blot and FCM assay were used to evaluate the antiviral effect of TTO against VSV under 3 modes of pre-infection before medication, co-administration, pre-treatment before infection at safe doses to Vero cells. Meanwhile, the mRNA expressions of IL-8, TNF-α and ISG56 in cells were also detected. The results showed that the maximum safe concentration of TTO to Vero cells was 0.063%, and the TCID50 was 10-7.375. Most notably, TTO significantly restrained the replication of VSV in gene and protein levels in a dose-dependent manner regardless of the treatment modes. Similarly, the mRNA expression of inflammatory cytokines induced by viral infection was also remarkably curbed. These findings suggested TTO emerged disinfection, prophylaxis and treatment action against VSV infectivity and suppressed the related inflammation in Vero cells. This study provides a novel potential for TTO fighting against viral infection, and the mechanism and in vivo effects need further analysis.